Peran Pastry dan Bakery terhadap Kepuasaan Pelanggan di Toko Deli Hotel Majapahit Surabaya - Intan Normalita Sari; I Ketut Suardana (Journal of Tourism and Creativity, 2021)
The purpose of this research are (1) To find out how to good work and professionally the staff Deli Store Majapahit Hotel which can increase customer satisfaction And (2) to meet customer desires in purchasing Pastry and Bakery products from Deli Store Majapahit Hotel. The method used is the method of data analysis with descriptive quantitative methods and methods of data collection by observation, interviews, and documentation. The results of the study (1) the management of Deli Store Hotel Majapahit, will guide the new employe for two weeks to learn about the Bakery product and customer service, so the customer will be happy and satisfied about our service when buying our product. And giving the information about Deli Store Majapahit Hotel customer loyalty were the customer will always get the best service and always satisfied about our service. (2) the customer loyalty Deli Store Majapahit Hotel will get discount for every product and always get the best service so the other customer want to be customer loyalty.